Highly efficient method for 125I-radiolabeling of biomolecules using inverse-electron-demand Diels–Alder reaction. Issue 11 (1st June 2016) - Choi, Mi Hee; Shim, Ha Eun; Yun, Seong-Jae; Kim, Hye Rim; Mushtaq, Sajid; Lee, Chang Heon; Park, Sang Hyun; Choi, Dae Seong; Lee, Dong-Eun; Byun, Eui-Baek; Jang, Beom-Su; Jeon, Jongho
Graphical abstract: Abstract: In this report, we present a rapid and highly efficient method for radioactive iodine labeling of trans -cyclooctene group conjugated biomolecules using inverse-electron-demand Diels–Alder reaction. Radioiodination reaction of the tetrazine structure was carried out using the stannylated precursor2 to give 125 I-labeled product ([ 125 I]1 ) with high radiochemical yield (65 ± 8%) and radiochemical purity (>99%). For radiolabeling application of [ 125 I]1, trans -cyclooctene derived cRGD peptide and human serum albumin were prepared. These substrates were reacted with [ 125 I]1 under mild condition to provide the radiolabeled products [ 125 I]6 and [ 125 I]8, respectively, with excellent radiochemical yields. The biodistribution study of [ 125 I]8 in normal ICR mice showed significantly lower thyroid uptake values than that of 125 I-labeled human serum albumin prepared by a traditional radiolabeling method. Therefore [ 125 I]8 will be a useful radiolabeled tracer in various molecular imaging and biological studies. Those results clearly demonstrate that [ 125 I]1 will be used as a valuable prosthetic group for radiolabeling of biomolecules.